Usefulness of Bioindicators and Biomarkers in Pollution Biomonitoring - Hamza-Chaffai, Amel (International Journal of Biotechnology for Wellness Industries, 2014)
We have different possibilities and tools to assess the impact of pollution on marine ecosystems. The ecotoxicological approaches are based on the use of biomonitors and biomarkers. They aim to study the effect of toxic chemicals on the biological organisms especially at the population, community and ecosystem levels. The ultimate goal of ecotoxicology is to be able to predict the effects of pollution so that the most efficient and effective action to prevent or remediate any detrimental effect. In order to assess the impact of anthropogenic activities on the aquatic ecosystem and to insure compliance with regulation or guidelines, we use biomonitoring. This kind of approach is based on the use of biological responses in order to assess anthropogenic changes in the environment. Biomonitoring involves the use of indicator species such as filter feeding mollusk bivalves. These organisms tend to accumulate pollutants in their tissues without showing any apparent detrimental effect. Moreover, they could reflect the real bio available fraction of the pollutant. In order to have an early warning system predicting the pollution effects even at low levels, biomarkers were extensively studied. Some of them were validated in both field and in vivo conditions. In the present paper, the usefulness of bioindicators and biomarkers in pollution monitoring are discussed. An overview of results from case studies dealing with in situ, in vivo and transplantation experiments is presented.